ANALISIS PENGARUH BRAND IMAGE TERHADAP RE-VISIT INTENTION RUMAH SAKIT PONDOK INDAH YANG DI MEDIASI OLEH SERVICE QUALITY - Herwanda Aditya; Efendi Efendi (Prosiding Working Papers Series In Management, 2017)
Pondok Indah Hospital is a hospital that provides many choices of patient needs in the form of emergency primary services, executive health, medical check up, out patient, in patient and diagnostic. And there is also a 24-hour prescription service with computerized services on pharmacy, an emergency guaranteeing the availability, quality and accuracy of the drug for patients. Pondok Indah Hospital was first established in Indonesia in 1986 in Pondok Indah. This study aims to determine the effect of brand image on re-visit intention at Rumah Pondok Indah Hospital can be mediated by Service Quality. Data were obtained by spreading 150 questionnaires to patients who visited Pondok Indah Hospital. The sampling technique used in this research is non random sampling. Results of data processing using SPSS 23 for windows with macro Hayes 2013. The results of this study indicate that there is influence of brand image to service quality, there is influence from service quality to loyalty re-visit intention, there influence of brand image to loyalty re-visit intention, and service quality mediate influence of brand image to loyalty re-visit intention.Keywords: Brand Image, Service Quality, Re-Visit Intention